Correlation between WDF, WNR, and RET Abnormal Scattergram Detected by Sysmex XN-1000 and Parasitemia of Malaria Patients in Merauke Hospital - Merylin Ranoko; Aryati Aryati; Arifoel Hajat (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
Malaria remains a health problem in Indonesia. Microscopic examination with Giemsa staining is the gold standard for diagnosing malaria. The density of parasites correlates with the degree of severity and response to therapy of malaria. Malaria-causing plasmodium can be detected by Sysmex XN-1000 which is marked by abnormalities in the WDF, WNR and RET scattergram. This research aimed to determine the correlation of WDF, WNR and RET abnormal scattergram detected by Sysmex XN-1000 and the parasitemia index of malaria at the Merauke General Hospital. This was a cross-sectional study with observational approach conducted between November 2017 – February 2018 at the Merauke General Hospital. Positive malaria samples were stained with Giemsa, their parasitemia index was calculated, routine complete blood count using Sysmex XN-1000 was performed, and the scattergram abnormalities were then analyzed. There were 65 positive malaria samples as follows: P.falciparum (35%), P.vivax (60%), P.ovale (3.1%), and P.malariae (1.5%), but the species did not correlate with parasitemic index (p=0.691). Abnormalities of WDF and WNR scattergram were predominantly found than RET scattergram (80% vs. 27.7%). P.vivax predominantly caused abnormalities of the WDF and WNR scattergram in 36 of 39 samples (92.3%), whereas P.falciparum predominantly caused abnomalities of the RET scattergram in 14 of 23 samples (60.9%). There was 95% positivity of an abnormality in WDF/WNR/RET scattergram with a cut-off of > 5,0165.5/µL. There was correlation between WDF, WNR, RET scattergram detected by Sysmex XN-1000 and the parasitemia index.